Philosophy for Children Curriculum as the Introduction to Liberal Education - Zuzanna Sury (Nicolaus Copernicus University in Toruń, 2014)
The paper shows some elements of liberal education in 'Philosophy for children' curriculum. The curriculum helps in teaching philosophy at every level of education. The argumentation refers to Leo Strauss and his concept of 'greatest books', to 'multiculturalism' of Martha Nussbaum and to 'critical thinking' of John Henry Newman. The paper describes the aims, goals, objectives and methodology of teaching in the curriculum and shows the components which are typical for liberal education.